Behind the Scenes: Gender Equality in Local Union Leadership - Bernard Pelletier, Marie-Pier; Le Capitaine, Catherine (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l’Université Laval, 2023)
AbstractThis article examines the experiences of local union presidents with respect to gender equality. Based on a qualitative case study of members of union committees dedicated to the status of women and local union presidents working in the Québec education sector, our research points to an unprecedented breakthrough of women serving as local presidents. Nevertheless, the existence of a “triple burden,” the persistence of gender stereotypes and a male union culture, the lack of training and mentoring, and the reliance on solicitation are all hindering the achievement of gender equality. Our research findings also highlight a weak representation of the diversity of social identities within the union organization studied.SummaryThis article examines the experiences of local union presidents with respect to gender equality. In a context where equity, diversity and inclusion in the workforce are more relevant than ever, this paper aims to contribute to reflections on the democratic deficit of female representation in union organizations. The findings are based on a qualitative case study of members of two union committees dedicated to the status of women and sixteen local union presidents working in the Québec education sector. By gathering the views of these women and men, our research makes a case for the long-neglected place of women serving as local presidents within the union organization studied. It is the efforts made by the unions themselves that have gradually allowed women to enter the traditionally male-dominated union world. Behind this unprecedented breakthrough, however, are gaps that remain in achieving gender equality. Beyond a continuing numerical deficit of women, the difficulty of managing a “triple burden,” the persistence of gender stereotypes, the prevalence of a male union culture, the lack of training and mentoring, and the use of solicitation are major obstacles that prevent women from accessing local union leadership positions. In addition, the representation of diverse social identities (age, family status, race, etc.) is still not well represented at the local decision-making level of the union organization studied, even among elected women. Diversity and gender equality representation remain challenges to be prioritized to ensure a more sustainable and democratic union organization.